Modern approaches to the choice of treatment tactics in patients with cervical cancer - A. L. Chernyshova; L. A. Kolomiets; Yu. M. Trushchuk; O. V. Shpileva; E. V. Denisov; I. V. Larionova; Zh. A. Startseva; V. I. Chernov; E. S. Marchenko; T. L. Chekalkin; V. A. Antipov; S. E. Krasilnikov (ABV-press, 2021)
Currently, approaches to the choice of treatment tactics for cervical cancer have changed significantly. According to the recommendations of ESGO (2018), RUSSCO (2020), the use of a combination of surgical treatment and radiation therapy significantly increases the incidence of complications. Therefore, when planning the treatment of patients with IB1-IIA1, a combination of surgical treatment and radiation therapy should be avoided. The article presents an analysis of modern approaches to the treatment of initial, locally advanced and advanced cervical cancer. Modern approaches to organ-preserving treatment are considered, including the view from the point of view of expanding the indications for trachelectomy as part of combined treatment. The question of the expediency of using hyperthermia and indications for this type of treatment in combination with radiation therapy is considered. The author presents his own view of the problem as a whole and possible ways to solve this problem.